Frontispiece: Materials Formed by Combining Inorganic Glasses and Metal‐Organic Frameworks. Issue 38 (6th July 2022) - Chester, Ashleigh M.; Castillo‐Blas, Celia; Wondraczek, Lothar; Keen, David A.; Bennett, Thomas D.
Abstract : The formation of hybrid materials through the combination of the chemically versatile, functional metal‐organic framework (MOF) family is proposed, with ubiquitous, low cost and durable inorganic glasses. The blends and composites hence created may serve to minimise, and eventually solve cost, durability and processability issues of MOFs, whilst retaining their valuable properties.